Estrogen levels in surface sediments from a multi-impacted Brazilian estuarine system - Pusceddu, Fabio Hermes; Sugauara, Lucy Elaine [UNESP]; Marchi, Mary Rodrigues de [UNESP]; Choueri, Rodrigo Brasil; Castro, Italo Braga (Elsevier B.V., 2019)
Estrogen levels were assessed in surface sediments from one of the most industrialized and urbanized estuarine systems in Latin America (SSES, Santos and Sao Vicente estuarine system). Estriol (E3) presented quantifiable levels in all sampled sites, ranging from 20.9 ng g(-1) to 694.2 ng g(-1). 17 beta-estradiol (E2) and 17 alpha-ethinylestradiol (EE2) were also detected in almost all sampled sites. The highest concentration of E2 was 23.9 ng g(-1), whereas high levels of EE2 86.3 ng g(-1). The occurrence of estrogens in SSES was diffuse and partially related to a domestic sewage outfall. Estrogens were also found in areas with substantial contribution of sanitary effluents from domiciles not covered by sanitation services. Our results reinforce that studies on environmental contamination by estrogens should not be spatially limited to the vicinities of point sources. These results contribute to raise awareness on the need of a formal approach to assess ecological risks of estrogens in the SSES.
Keywords: Contamination; Estriol; 17 beta-estradiol; 17 alpha-ethinylestradiol; Sewage; Endocrine disruptors